DENSIDAD FONONICA Y POTENCIAL DE DEFORMACION - Salazar de Paz, Luis (2006)
On the latest decades it had developed computer methods for simulation of liquid and amorphous system methods using potential pairs for total energy formulation of a particular substance with real space methods. Ashcroft and Stroud introduced simple pseudo potentials on the theoretical formulation of first beginnings, for pair potential calculation; the application for that had restricted only in a few simple metallic systems. The treatment with phonons is used on the determination of a series of physical properties. On this work it looks the solids from a point of view of the phonon’s aspects. The intention is to contribute on the description of a model that assists to determinate the elastic properties of the solids by non-classics methods.